PREFERENCE LEVEL OF PUFF PASTRY WITH THE ADDITION OF TILAPIA FLUOR - Fiza Jasmine Hasani; Rusky Intan Pratama; Fittrie Meylianawaty Pratiwy; Iis Rostini (Jurnal Perikanan Unram, 2024)
Increasing the protein content in Puff Pastry can be done by adding nila fish meat flour. This research aims to determine the percentage of nila fish meat flour addition level in making puff pastry products that are most preferred by the panelists. The study was conducted from February to March 2024 at the Fisheries Product Processing Laboratory, Faculty of Fisheries and Marine Sciences, Padjadjaran University. The method in this research is experimental with 4 treatments of nila fish meat flour addition at 0%, 2.5%, 5%, 7.5% of the weight of wheat flour. The parameters observed were hedonic test with levels of preference for appearance, aroma, texture, and taste conducted on 25 semi-trained panelists who are students of the Faculty of Fisheries and Marine Sciences. The next parameter is proximate testing for the control treatment and the most preferred one, determining the protein content, water content, ash content, fat content, and carbohydrate content. The research results conclude that the addition of 2.5% nila fish meat flour is the most preferred treatment based on hedonic test with median values of appearance 7, aroma 7, taste 9, texture 9, and alternative value 8.57 and has a protein content of 8.74%, water content of 1.48%, ash content of 1.80%, fat content of 38.64%, and carbohydrate content of 47.12%. Keywords: hedonic, proximate, fish protein, preference level